Comparing simplification and image-based techniques for 3D client-server rendering systems - Pasman, W.; Jansen, F.W. (IEEE transactions on visualization and computer graphics, 2003)
A mathematical model is presented for comparing geometric and image-based simplification methods. Geometric simplification reduces the number of polygons in the virtual object and image-based simplification replaces the object with an image. Our model integrates and extrapolates existing accuracy estimates, enabling the comparison of different simplification methods in order to choose the most efficient method in a given situation. The model compares data transfer and rendering load of the methods. Byte size and expected lifetime of simplifications are calculated as a function of the desired visual quality and the position and movement of the viewer. An example result is that, in typical viewing and rendering conditions and for objects with a radius in the order of one meter, imposter techniques can be used at viewing distances above 15 meters. Below that, simplified polygon objects are required and, below one meter distance, the full-resolution virtual object has to be rendered. An electronic version of the model is available on the web.